PROFIL PERILAKU HETEROSEKSUAL SEHAT REMAJA DI SMP NEGERI 4 HILIRAN GUMANTI KABUPATEN SOLOK - Nofridawati, Nofridawati; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
This study profiles describe about healthy adolescent heterosexual behavior in Junior High School 4 Hiliran Gumanti District. Focused on sexual feelings shown to the opposite sex and sexual interest in the opposite sex shown in this study is a population of students numbering 68 people, sampling in this study uses total sampling technique. Data collection instruments used questionnaires and the data processed using the percentage formula. The findings of the study revealed that healthy heterosexual adolescent behaviors include: (1) Acquire knowledge and sex roles conformed to gender, including the pretty good category, (2) Develop a positive attitude toward sex, including the pretty good category, (3) Learning to behave according to the heterosexual norm, including the pretty good category, (4) Setting the values in choosing a life partner, including the fair category, (5) Learning to express love, including the pretty good category, (6) development of heterosexuals, including the category quite well, (7) a new heterosexual pattern, including both categories. This study is expected to provide an overview of the types of service in developing a healthy heterosexual behavior in school counselor. Add new insights regarding the development of learners heterosexual adolescents. Parents can develop adolescent heterosexual behavior in Kanagarian Sariak Alahan Tigo into a more positive direction. Niniak Mamak Kanagarian Sariak Alahan Tigo Jorong Talaok can assist youth in developing as well as the development of heterosexual heterosexual behavior can be a good example for young people in kanagarian in Junior High School 4 Hiliran Gumanti District.